Pengaruh Motivasi, Kerjasama Tim terhadap Kinerja Pegawai Melalui Komitmen di Universitas Prima Indonesia - Lenta Friska Purba (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2022)
This research is an associative research type with a quantitative approach conducted at the University of Prima Indonesia. This study aims to determine and analyze the effect of motivation and teamwork on performance through commitment. The data collection method in this study was a questionnaire or questionnaire. The sampling technique used is the Random Sampling technique. The population that became the object of research was 182 UNPRI employees with a sample of 85 employees. Hypothesis testing is done by path analysis. Based on the results of the study with a significant level of 5%, the conclusions were: (1) Motivation had a direct positive effect on employee commitment of 0.776 (2) Teamwork had a direct positive effect on employee commitment of 0.145. (3) Motivation has a direct positive effect on performance of 0.366. (4) Teamwork has a direct positive effect on performance of 0.339. (5) Commitment has a direct positive effect on employee performance of 0.592. (6) Motivation through commitment has a positive effect on employee performance by 0.326. (7) Teamwork through commitment has a positive effect of 0.168. Keywords: Motivation, Teamwork, Commitment, Performance